(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2025)
This research aims to determine the regional government’s strategy in dealing with early marriage in Barru Regency. The type of research used is qualitative research, data collection uses observation, interview and documentation techniques. The results of the research show that the regional government’s strategy in dealing with early marriage in Barru Regency is considered optimal, where the rate of early marriage will decrease in 2022 after experiencing an increase in 2021. Strength, with the presence of religious counselors in each sub-district and the involvement of parents and teenagers . In terms of weaknesses, there are still many people who hold strong traditions and have a low level of understanding regarding the risks of early marriage. Furthermore, from an Oppertunity perspective, this strategy is not only implemented by one element but certainly involves others such as the community and also the relevant regional government. The last one is Thearth, where the divorce rate, poverty and educational backwardness are increasing. The internal factor that influences this research is laziness.